The Auditory Middle Latency Response, Evoked Using Maximum Length Sequences and Chirps, as an Indicator of Adequacy of Anesthesia - Bell, Steven L.; Smith, David C.; Allen, Robert; Lutman, Mark E. (Anesthesia and analgesia, 2006)
The auditory evoked potential known as the middle latency response (MLR), evoked with regular click stimulation at around 5 Hz, has been suggested as an indicator of adequacy of anesthesia. The MLR is a very small signal embedded in high levels of background noise, so it can take a long time to acquire. However, using a stimulus paradigm of chirps presented in a maximum length sequence, the acquisition of the MLR can be improved compared to using conventional click stimulation. In this pilot study, we investigated this new technique in a clinical environment. Significant changes in MLR amplitude, but not latency, were measured for six of seven subjects in association with changes in responsiveness to command using the isolated forearm technique. The absence of any latency shift differs from other studies of the MLR during anesthesia and highlights the limited understanding of the relationship between anesthesia and the MLR.